4+3x-1=9x+11-5x

Simple and best practice solution for 4+3x-1=9x+11-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+3x-1=9x+11-5x equation:


Simplifying
4 + 3x + -1 = 9x + 11 + -5x

Reorder the terms:
4 + -1 + 3x = 9x + 11 + -5x

Combine like terms: 4 + -1 = 3
3 + 3x = 9x + 11 + -5x

Reorder the terms:
3 + 3x = 11 + 9x + -5x

Combine like terms: 9x + -5x = 4x
3 + 3x = 11 + 4x

Solving
3 + 3x = 11 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
3 + 3x + -4x = 11 + 4x + -4x

Combine like terms: 3x + -4x = -1x
3 + -1x = 11 + 4x + -4x

Combine like terms: 4x + -4x = 0
3 + -1x = 11 + 0
3 + -1x = 11

Add '-3' to each side of the equation.
3 + -3 + -1x = 11 + -3

Combine like terms: 3 + -3 = 0
0 + -1x = 11 + -3
-1x = 11 + -3

Combine like terms: 11 + -3 = 8
-1x = 8

Divide each side by '-1'.
x = -8

Simplifying
x = -8

See similar equations:

| 0.16(24)+0.04x=0.08(18+x) | | -(6x+3)-(8x-7)=8-(5x+1) | | 6m-8=2+9m-6 | | 10-4x=-2+8x | | 2x+13=37 | | 3t=1 | | 4y-12=-3y | | [x]-y=2 | | 3t=-1 | | 4x+43x+30x=0 | | 2y=1-xy | | 1-0x=0 | | .14y+6=-19 | | 3x-2x=6 | | 15+k=-9 | | b+2b+(b+15)=95 | | 6=13+q | | 11z=-33 | | 6(-4)= | | 8*-7= | | (x^2)=-4 | | y+23=-1 | | -29+q=4 | | (2x+6)*(x+5)=a | | d-4=-25 | | 5(2x-3)+7=10x-8 | | (x+100)+(x)+(x-50)=500 | | -7=7+n | | (x+12)2=196 | | q-24=-20 | | r(x)=x^2+4x-32x-8 | | (x^2)+5x+4=0 |

Equations solver categories